APLIKASI SIG DALAM PENELITIAN GEOLOGI - -, Emi Sukiyah (Bulletin of Scientific Contribution, 2013)
Explorative and descriptive are typical research of geology. Quantitative analysis is limited whereas cost research is expensive. Actually, there are some aspects of geology require quantitative analysis, mainly in vertical and lateral distribution. They need tool for do it.Several quantitative themes of geological research are slope analysis, erosion-sedimentation calculation, calculation of minerals proportion, calculation of chemical elements proportion, calculation of drainage density, calculation of fracture, etc. They need powerful tool for support data analysis with high accuracy.Many soft ware of data processor are available. They include graphical and non-graphical data. We can use that soft ware as tool for data analysis. Nevertheless, a part of them have limited in integrated data analysis. Commonly, Geographic Information System (GIS) soft ware can become choice. The available specification comprehension of soft ware can upgrade quality of data analysis.